2008
DOI: 10.1364/oe.16.019493
|View full text |Cite
|
Sign up to set email alerts
|

Numerical method for high accuracy index of refraction estimation for spectro-angular surface plasmon resonance systems

Abstract: An eigenvector analysis based algorithm is presented for estimating refractive index changes from 2-D reflectance/dispersion images obtained with spectro-angular surface plasmon resonance systems. High resolution over a large dynamic range can be achieved simultaneously. The method performs well in simulations with noisy data maintaining an error of less than 10(-8) refractive index units with up to six bits of noise on 16 bit quantized image data. Experimental measurements show that the method results in a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…It has previously been shown that this method depends greatly on both the resolution of the camera and even more significantly on the bit depth of the data acquisition. 11 A spectro-angular SPR system built in our laboratories with a light source at 850 nm and the detection limit of the system, 1.5 × 10 −6 RIU, was found to be close to the predicted detection limit for the camera resolution and bit depth. 10 In order to improve the detection limit of the SPR biosensor, we sought to employ image sensors with greater bit depth and more pixels.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…It has previously been shown that this method depends greatly on both the resolution of the camera and even more significantly on the bit depth of the data acquisition. 11 A spectro-angular SPR system built in our laboratories with a light source at 850 nm and the detection limit of the system, 1.5 × 10 −6 RIU, was found to be close to the predicted detection limit for the camera resolution and bit depth. 10 In order to improve the detection limit of the SPR biosensor, we sought to employ image sensors with greater bit depth and more pixels.…”
Section: Introductionsupporting
confidence: 56%
“…The details of the DPM method are described in Alleyne et al 11 Briefly, this method employs a set of tion is performed; the matrix of reflection images is projected on the SVD processed matrix to obtain the basis set. With the basis set in memory, every image of unknown refractive index is rearranged into a column vector and is projected against the SVD processed matrix creating a weight vector.…”
Section: Comparison Of Visible and Infrared Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the involvement of more complicated experimental arrangements for simultaneous collecting of angularspectral data, such approach demonstrated an improvement in resolution of imaging schemes [38]. In addition, angular-spectral interrogation renders possible the application of novel advanced algorithms for the treatment of signals, yielding potentially to a much lower detection limit for refractive index estimation [39].…”
Section: Surface Plasmon Resonance: Phase Vs Amplitudementioning
confidence: 99%
“…The increase ( ) in the spatial RI profile and the waveguide core dimensions can be estimated by different techniques, such as reflectivity method [2], scattering pattern [3], surface plasmon resonance [4], prism coupling [5,6], surface topography [7], refraction method and estimate from near field profile (NFP) [8,9]. An inversion of the scalar wave equation to estimate the dimensions and the RI profile of the waveguide is possible with good signal noise ratio NFP [10].…”
mentioning
confidence: 99%